Sosialisasi Konsep Komunikasi Digital Dalam Pembangunan Desa Cerdas di Desa Sungai Petai (Jurnal Abdimas STMIK Dharmapala, 2024)
One concept of village development that is suitable for the current era is the concept of a smart village, namely the concept of village development by utilizing digital technology both for public services and regional development such as infrastructure, information technology, communication technology.Villages have extraordinary differences in characteristics to realize a smart village. Differences in geographical conditions, customs, or the culture of the population characterize the development of smart villages. Smart villages certainly have different problems that seem impossible to solve with one uniform solution for all villages in Indonesia. Likewise, the development potential of the smart village is also very diverse from the aspect of agriculture, tourism, mining, or energy. This paper aims to provide knowledge to the Sungai Petai Village government, Kampar Kiri Hilir District, Kampar Regency, Riau Province so that they can utilize digital communication concepts in planning programs towards smart villages and make it easier for village governments to coordinate with related parties. The results of this socialization are expected to be able to implement the concept of a digital village in the implementation of the government so that the village of Sungai Petai is able to be realized